2020
DOI: 10.1111/joim.13066
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term changes in adipose tissue gene expression following bariatric surgery

Abstract: Long-term changes in adipose tissue gene expression following bariatric surgery (Original Article).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 49 publications
(66 reference statements)
4
34
0
Order By: Relevance
“…[105][106][107] Some bariatric surgery patients regained weight after weight loss, but the inflammatory factors continued to decrease, indicating that bariatric surgery may have a long-term effect on inflammation control. 108…”
Section: Anti-inflammatory Therapeutic Effect Of Bariatric Surgerymentioning
confidence: 99%
“…[105][106][107] Some bariatric surgery patients regained weight after weight loss, but the inflammatory factors continued to decrease, indicating that bariatric surgery may have a long-term effect on inflammation control. 108…”
Section: Anti-inflammatory Therapeutic Effect Of Bariatric Surgerymentioning
confidence: 99%
“…Genes previously identified as differentially expressed in SAT following bariatric surgery are involved in lipid and energy metabolism, inflammatory and immunological responses, insulin signaling, cell differentiation, oxidative stress regulation and gene transcription [ 27 , 30 ]. A recent study [ 32 ] has also observed long-term effects of RYGB on gene expression in abdominal SAT, with enriched pathways related to lipid metabolism, fat cell differentiation and immune response. Again, most of the studies examining gene expression changes in SAT have been conducted among individuals with obesity who had undergone RYGB or SG, but none had investigated the impact of BPD-DS on the transcriptomic SAT profile [ 27 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 7,729 early and maintained DMS were compared to 4,128 genes reported to show early response or continual change in expression in one direction after bariatric surgery in the same cohort 8 . This identified 1,259 differentially expressed genes with DMS (Supp.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in peripheral organs are also likely involved in the regulation of metabolism. For example, bariatric surgery results in early and continued decrease in SAT inflammatory gene expression and release of cytokines as well as development of a hyperplastic adipose tissue (many but small fat cells), which is considered to be a benign adipose morphology 8 . The present study suggests that improvement of fat cell lipogenesis is an additional long-term beneficial effect of bariatric surgery.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%